Embedded intelligent riding platform based on FreeRTOS - Yu Xinyi; Zhao Jianan; Ying Haozhe; Ou Linlin; Feng Yuanjing (Dianzi Jishu Yingyong, 2022)
In order to solve the problems of the traditional non-intelligent cycling platform with single function, no data interaction with the cycling platform client, uneven resistance adjustment, general riding experience, an embedded intelligent riding platform based on FreeRTOS real-time operating system is designed. The design scheme of riding resistance selects the magnetoresistive type, which aims to reduce the noise and improve the riding experience. In terms of hardware circuit, the main control module, power supply module, speed measurement module and magnetoresistance control module are designed according to the functional needs of the system. The program design part includes Bluetooth communication, ANT+ communication, speed calculation, power fitting, sleep and wake-up, and magnetoresistance control. Finally, an experimental device is made to test the wireless communication function, gear control function, and client adaptation function of the riding platform. The experimental results show that, the system has good real-time performance and high reliability, which can meet the preset functional requirements.